Experimental study of the influence of non-sinusoidal voltage on no-load losses of transformers - A. V. Petrov; V. E. Martusenko; K. S. Gordienko; V. V. Redkin (Вестник Северо-Кавказского федерального университета, 2023)
The study of the influence of higher harmonics on the value of the no-load losses of transformers is carried out. The description of an experimental setup for determining the value of idling losses at various levels of non-sinusoidality and phase ratios of higher harmonics is given. Experimental studies of the influence of the frequency and the initial phase of the higher harmonics in the voltage spectrum on the value of the transformer idling losses have been carried out.